The Racialization of Islam in the United States: Islamophobia, Hate Crimes, and “Flying while Brown” - Considine, Craig (Religions (Basel, Switzerland ), 2017)
This paper explores the intersectionality of race and Islamophobia by using a set of empirical data relating to the experiences of American Muslims and non-Muslims in the United States. Through a multi-tiered methodology, the paper reveals how racialization processes interact with Islamophobic discourses and actions in American society. Specifically, the dataset is anchored in U.S. public perceptions of American Muslims, hate crime incidents against Muslims and non-Muslims, and the institutionalization of Islamophobia. The paper, which shows how race is endemic to Islamophobic incidents, appeals to the general U.S. public, especially community members from religious, political, academic, civil rights, and social justice backgrounds.